2020
DOI: 10.3390/ph13050084
|View full text |Cite
|
Sign up to set email alerts
|

A Polyphenol-Rich Fraction from Eugenia uniflora Exhibits Antioxidant and Hepatoprotective Activities In Vivo

Abstract: Leaves from Eugenia uniflora, the red Brazilian cherry, have a high content of flavonoids that possess several biological effects such as anti-inflammatory, antioxidant, and antidiabetic activities. However, their influence on carbon tetrachloride (CCl4)-induced acute liver injury in rats has not been investigated. In the current study, a bioguided fractionation assay revealed that the ethyl acetate fraction (EAF) of Eugenia uniflora is the safest and most active fraction. LC-MS analysis of the ethyl acetate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 37 publications
(46 reference statements)
2
14
0
2
Order By: Relevance
“…This efficacy could be attributed to its high phenolic content, which was assayed by Folin Ciocalteu method; it represented 312 mg gallic acid equivalents/ g extract. The obtained results come in agreement with numerous plant extracts rich in polyphenols ( Sobeh et al, 2019 , Sobeh et al, 2020 , El-Hawary et al, 2020a ).…”
Section: Resultssupporting
confidence: 89%
“…This efficacy could be attributed to its high phenolic content, which was assayed by Folin Ciocalteu method; it represented 312 mg gallic acid equivalents/ g extract. The obtained results come in agreement with numerous plant extracts rich in polyphenols ( Sobeh et al, 2019 , Sobeh et al, 2020 , El-Hawary et al, 2020a ).…”
Section: Resultssupporting
confidence: 89%
“…In addition, myricetin was first discovered by Spanier for its activation of DAF-16 and its increase in the expression of its downstream gene sod-3 , but it was found that the activation of DAF-16 was not the cause of the extended lifespan because it was found that DAF-16 activation was not correlated with the myricetin-mediated decrease in mitochondrial ROS and the increase in longevity (Grunz et al, 2012 ). However, further experiments proved that myricetin does exert its anti-oxidant effect through DAF-16 (Buchter et al, 2013 ; Sobeh et al, 2020 ). All these studies found that, in DAF-16 mutants, the ROS-scavenging effect of myricetin was blocked to a great extent, and the beneficial effect on lifespan also disappeared completely.…”
Section: Flavonolsmentioning
confidence: 99%
“…SOD is the main antioxidant enzyme that eliminates these free radicals and limits hepatic damage. MDA, the final product of lipid peroxidation, is a biomarker of oxidative stress ( Sobeh et al, 2020 ; Zhang et al, 2020 ). The results show that SCU significantly enhances SOD activity and attenuates MDA production relative to the CCl 4 group.…”
Section: Discussionmentioning
confidence: 99%